Ethical challenges in counseling and solving it - Mohammad Reza Salarifar (اخلاق وحیانی, 2022)
This study examines the ethical challenges of counseling and ways to solving it. The ethical challenge of counseling; It is a clinical situation for which no option seems satisfactory, and the counselor, as a moral agent, simultaneously has two or more moral duties to the client, each of which is his sole duty, but because of the simultaneity he can not perform them all. The research method includes two approaches of observing ethical principles and theories and considering all dimensions in a case, which is called thoughtful balance. Based on research findings; Solving an ethical challenge in counseling involves six steps. This method was used to solve the following ten types of ethical challenges in counseling: Admitting a client for counseling, sexual issues, religiosity, mental disorders and tests, legal issues, marriage counseling, couple therapy, infidelity, divorce and child counseling